2014
DOI: 10.11138/per/2014.3.4.137
|View full text |Cite
|
Sign up to set email alerts
|

Return to work after an acute cardiac event: the role of psychosocial factors

Abstract: Introduction: long-term sick leave is currently a considerable public health concern due to the enormous financial consequences for society. Return to work (RTW) after a cardiac event is a major goal of cardiac rehabilitation because it improves patients' quality of life and economic security, and reduces occupational disability costs. The aim of this article is to review the current and main psychosocial factors influencing the RTW process among cardiac patients. Materials and Methods: the review is based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 46 publications
(102 reference statements)
0
13
1
Order By: Relevance
“…workplace stress, workplace social support, job satisfaction, motivation to resume work), which are critical issues in understanding the duration of sickness absence and health risks associated with return to work. 49 Second, the finding that psychosocial factors were not associated with return to work in our study was surprising, as they were shown to be more important than conventional clinical factors in previous studies. 1 This difference in findings may be due to the fact that we used baseline psychosocial factors to predict 1-year outcomes.…”
Section: Discussioncontrasting
confidence: 67%
“…workplace stress, workplace social support, job satisfaction, motivation to resume work), which are critical issues in understanding the duration of sickness absence and health risks associated with return to work. 49 Second, the finding that psychosocial factors were not associated with return to work in our study was surprising, as they were shown to be more important than conventional clinical factors in previous studies. 1 This difference in findings may be due to the fact that we used baseline psychosocial factors to predict 1-year outcomes.…”
Section: Discussioncontrasting
confidence: 67%
“… 3 , 7 Moreover, our study shows that negative psychological factors turned out to be determinants of the detachment from employment at one- and two years of follow-up: negative expectations concerning return-to-work, daily functioning, and depressive symptoms, all congruent with the findings of other studies. 8 , 16 , 29 , 30 Nonetheless, the intervention programs proved to be a powerful determinant of long-term employment over and above the demographic, occupational, and psychological factors.…”
Section: Discussionmentioning
confidence: 99%
“…blue-collar work), and psychological factors (such as depression and expectations concerning work,. 3,[7][8][9][10][11][12] The significance of occupational assessment, provision of individualized clinical data, physical possibilities and vocational information has been shown to increase the return-to-work rate, promote early return-to-work, and reduce medical costs. [10][11][12] In their study, Froom et al have shown the importance of early intervention by showing a 30% decrease in the chance for full employment 24 months after an acute myocardial infarction for each month's delay in referral.…”
Section: Introductionmentioning
confidence: 99%
“…In a large number of studies, depression 10,13,24,27 and other mental comorbidities 6,10,24,29 have been suggested as a barrier for RTW, but to our knowledge we are the first to analyse depression/anxiety, using the HADS scale, in relation to RTW as an independent variable in a large CHD population.…”
Section: Discussionmentioning
confidence: 99%